2020
DOI: 10.1007/s10608-020-10149-6
|View full text |Cite
|
Sign up to set email alerts
|

Imagery Rescripting of Painful Memories in Social Anxiety Disorder: A Qualitative Analysis of Needs Fulfillment and Memory Updating

Abstract: Background: Imager rescripting (IR) is an effective intervention for social an iet disorder (SAD) that targets autobiographical memories of painful past events. IR is thought to promote needs fulfillment and memor updating b guiding patients to change unhelpful schema through addressing the needs of the ounger self within the memor . Methods: Qualitative coding was used to e amine the features of clinicall relevant strategies enacted during IR to fulfill needs and update memories in 14 individuals with SAD. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…As previous studies typically have not reported the used strategies qualitatively, the use of non-adaptive ImRs scripts may also have been a problem in earlier studies (e.g., Pennesi & Wade, 2018;Zhou et al, 2020). Indeed, a recent study in social anxiety explored the strategies that patients used during a single ImRs session and, strikingly, 43% of the participants chose at least one avoidant strategy even though in this study the ImRs was therapist guided (Romano et al, 2020). These findings highlight that for individuals prone to avoidance more guidance in rescripting may be necessary.…”
Section: Discussionmentioning
confidence: 87%
“…As previous studies typically have not reported the used strategies qualitatively, the use of non-adaptive ImRs scripts may also have been a problem in earlier studies (e.g., Pennesi & Wade, 2018;Zhou et al, 2020). Indeed, a recent study in social anxiety explored the strategies that patients used during a single ImRs session and, strikingly, 43% of the participants chose at least one avoidant strategy even though in this study the ImRs was therapist guided (Romano et al, 2020). These findings highlight that for individuals prone to avoidance more guidance in rescripting may be necessary.…”
Section: Discussionmentioning
confidence: 87%
“…Ten studies examined the impact of IR on encapsulated beliefs (Knutsson et al, 2019;Lee and Kwon, 2013;Nilsson et al, 2012;Norton and Abbott, 2016;Reimer and Moscovitch, 2015;Romano et al, 2020a;Romano et al, 2020b;Takanashi et al, 2020;Wild et al, 2007;Wild et al, 2008). Considering the four studies that performed pre-session versus within-session comparisons (Knutsson et al, 2019;Lee and Kwon, 2013;Wild et al, 2007;Wild et al, 2008), meta-analysis showed an overall decrease in encapsulated beliefs (WMD 29.74, 95% CI 24.34 to 35.13; SMD 0.62, Z = 10.80, p < 0.00001) and the presence of heterogeneity among studies (I 2 = 76%, p = 0.005) (Fig.…”
Section: Encapsulated Beliefsmentioning
confidence: 99%
“…Also, there were no significant differences among groups for updating core beliefs about others. Finally, in a qualitative follow-up study, Romano et al (2020b) interviewed 12 participants to understand their perception of memory changes due to IR. Nine participants reported changes in their experience of the memory as a result of IR, including changes in its emotional salience and/or its effect on their lives.…”
Section: Encapsulated Beliefsmentioning
confidence: 99%
“…The minority of studies which looked at beliefs associated with the rescripted memories (the “ encapsulated beliefs” ) showed reductions following ImRs. Subsequently published research has examined the effects of ImRs in binge eating disorder ( 4 ), obsessive-compulsive disorder ( 5 7 ), major depressive disorder ( 8 , 9 ), illness anxiety disorder ( 10 ), social anxiety disorder [SAD; ( 11 , 12 )], borderline personality disorder ( 13 ), psychosis ( 14 ), and voice hearers ( 15 ). Overall, this research supports previous findings on ImRs outcomes.…”
Section: Imrs As a Tool For Addressing Intrusive Mental Images In Clinical Disordersmentioning
confidence: 99%
“…At the same time, the new self-event connections, actively intervening in the memories, and imaginatively satisfying previously unmet needs may increase the sense of agency associated with these memories. Arntz and Weertman's ( 1 ) protocol explicitly incorporates need fulfillment and patients often employ memory intervention strategies which satisfy the needs they express in ImRs, including the need for autonomy [see ( 11 )]. The increased sense of agency and mastery may contribute to recovery, as demonstrated by evidence that change in mastery of nightmare content mediated the efficacy of ImRs on nightmare frequency and distress ( 47 ).…”
Section: A Narrative Identity Model Of Change In Imrsmentioning
confidence: 99%